Identification of Hotspots and Burnt Areas in Ogan Ilir District, South Sumatera Province - Febrida, Cely; Rejo, Amin; Husin, Azizah (Indonesian Journal of Environmental Management and Sustainability, 2024)
Ogan Ilir District is one of South Sumatra, Indonesia’s regencies, prone to forest and land fires. This study aims to identify hotspot distribution and analyze fire and land hazard levels from 2017 to 2022 in Ogan Ilir District using Landsat 8 imagery with the Normalized Burning Ratio (NBR) method. The study’s results show that from 2017 to 2022, 423 hotspots were recorded. Specifically, in 2017, there were 2 points; in 2018, 121 points; in 2019, 207 points; in 2021, 76 points; and in 2022, 17 points. North Indralaya is the sub-district with the highest level of forest and land fire vulnerability, with the number of events ranging from 80 to 164. West Pamulutan and Pamulutan are at a high hazard level, with incidents ranging from 33 to 79. Meanwhile, Indralaya and South Indralaya sub-districts have a medium level of danger, with events ranging from 19 to 32. The low threat level for forest and land fires is spread across all sub-districts in Ogan Ilir District, with the number of events ranging from 1 to 18.